Vegetation Owl Creek 4 - Sprague, Sallie, photographer (Colorado State University. Libraries, 2008)
Vegetation growing in Owl Creek south of ARS HQ where it goes under the road, part of panoramic series.
Keywords: SGS; vegetation; landscapes